The Impact Of Service Quality And Timeliness On Customer Loyalty In The Goods Delivery Service At J&T Express Sawahan Branch – Surabaya - Iqbal Yuniarko; Damajanti Sri Lestari; Liling Listyawati; Priyanto, Priyanto (Cita konsultindo, 2025)
This study investigates the impact of service quality and timeliness on customer loyalty in the context of J&T Express services in Surabaya. Employing a quantitative approach and survey method, data were collected from 96 respondents through electronically distributed questionnaires. The analysis included validity and reliability tests, linear regression analysis, and hypothesis testing using t-tests and F-tests. The findings indicate a significant positive influence of service quality and timeliness on customer loyalty. Specifically, service quality was found to play a crucial role in enhancing customer satisfaction, which in turn fosters loyalty. Additionally, the research underscores the need for J&T Express to improve service responsiveness and delivery accuracy to retain existing customers and attract new ones. This study contributes to understanding consumer behaviour in the logistics industry and provides actionable insights for improving service quality in similar service organisations.